2011
DOI: 10.1063/1.3657771
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent photoluminescence from porous silicon nanostructures: Quantum confinement and oxide related transitions

Abstract: Temperature dependent photoluminescence (PL) spectroscopy along with structural investigations of luminescent porous Si enable us to experimentally distinguish between the relative contributions of band-to-band and oxide interface mediated electronic transitions responsible for light emission from these nanostructures. Porous Si samples formed using high current densities (J ≥ 80 mA/cm2) have large porosities (P ≥ 85%) and consequently smaller (∼1-6 nm) average crystallite sizes. The PL spectra of these high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
(62 reference statements)
2
13
0
Order By: Relevance
“…14 Last, the difference between ME-and FS-prepared SiNCs can be further tested using the measurements of temperature dependence of PL. Several experiments 14,20,45,46 have already reported on the temperature dependence of PL for ME samples. All of them concluded that the PL blueshift with decreasing temperature behaves very similarly to that of bulk Si, i.e., that PL blueshifts by about 50 meV when the temperature drops from 300 to 3 K, see Fig.…”
Section: -3mentioning
confidence: 97%
“…14 Last, the difference between ME-and FS-prepared SiNCs can be further tested using the measurements of temperature dependence of PL. Several experiments 14,20,45,46 have already reported on the temperature dependence of PL for ME samples. All of them concluded that the PL blueshift with decreasing temperature behaves very similarly to that of bulk Si, i.e., that PL blueshifts by about 50 meV when the temperature drops from 300 to 3 K, see Fig.…”
Section: -3mentioning
confidence: 97%
“…Room‐temperature PL of the Si NCs is known to strongly depend on the molecular ambient 12 and the temperature 13, 14. Since high‐polar media (water, alcohol, etc.)…”
mentioning
confidence: 99%
“…Delerue et al [28] explain this hypothesis as it is the result of the radiative recombination of electron-hole pairs from the lowest exciton states whose binding energies are enhanced compared to bulk silicon. Also, the localized defect states at the interface between the nanocrystalline silicon and the surrounding oxide layer contribute to the PL signal in the visible range [29]. The reference sample that has undergone just a preoxidation at 300°C exhibits a broad PL peak centered around 2,1 eV.…”
Section: Band Gap Energymentioning
confidence: 99%